Can we improve breast cancer management using an image-guided histopathology workup supported by larger histopathology sections?. Issue 161 (April 2023) - Tabár, László; Dean, Peter B.; Lee Tucker, F.; Vörös, András
Highlights: Image assisted large format histopathology is a key component in patient management planning. Surgical margin determination is superior using the large format histopathology technique. Immunohistochemical and molecular biomarkers cannot compensate for the limitations of small section histopathology. Large format histopathology technique is less time-consuming and provides superior care at a lower cost. Histopathology technique and practice need to be reevaluated and modernized. Abstract: Purpose: Breast radiologists examine the entire breast in full-size images, while breast pathologists examine small tissue samples at high magnification. The diagnostic information from these complementary imaging approaches can be difficult to integrate for a more clinically relevant evaluation of malignancies spanning several centimetres. We have explored the advantages and disadvantages of imaging guided larger section pathology techniques compared with the standard 2 × 2.5 cm. small section technique. Methods: We compared the ability of conventional small section histopathology with larger section histopathology techniques to examine surgical resection margins and full disease extent. We evaluated the pre-surgical imaging workup and use of microfocus magnification radiography of sliced surgical specimens in the histopathologic evaluation of disease extent and status of surgical margins. Results: Image assisted large section histopathology of excised breast tissue enables comprehensive examination of an approximately tenfold larger contiguous tissue area than is provided by conventional small section technology. Attempting to cover the full area of each consecutive slice of resected tissue is more labour-intensive and expensive with the small section approach and poses challenges in reconstituting three-dimensional tumour architecture after morcellation and sectioning. Restricting histopathologic examination to a limited number of samples provides an incomplete evaluation of surgical margins. Conclusions: A considerably improved documentation of breast cancer and a more reliable assessment of tissue margins is provided by using larger sized histopathology samples to correlate with breast imaging findings. These in turn can enable more appropriate treatment planning, improved surgical performance, fewer recurrences, and better patient outcome. Uncertainty of surgical margin evaluation inherent to the standard small section technique can lead to inappropriate decisions in surgical management and adjunctive therapy. Progress in breast diagnosis and treatment will largely depend on whether histopathology terminology and technique will undergo a revolution similar to the one that has already occurred in breast imaging.